2012
DOI: 10.1073/pnas.1215858109
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish model for congenital myasthenic syndrome reveals mechanisms causal to developmental recovery

Abstract: Mutations in muscle ACh receptors cause slow-channel syndrome (SCS) and Escobar syndrome, two forms of congenital myasthenia. SCS is a dominant disorder with mutations reported for all receptor subunits except γ. Escobar syndrome is distinct, with mutations located exclusively in γ, and characterized by developmental improvement of muscle function. The zebrafish mutant line, twister , models SCS in terms of a dominant mutation in the α subunit (α twi ) but shows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 23 publications
(36 reference statements)
0
10
0
Order By: Relevance
“…The zebrafish mutants discussed in this review provided valuable insights into the pathophysiology of some neurological disorders. Sofa potato and twitch once had mutations in genes later identified to cause human diseases [ 13 , 24 , 25 , 40 ], and physiological study of twister indicated unappreciated benefits of subunit switch in myasthenic cases [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The zebrafish mutants discussed in this review provided valuable insights into the pathophysiology of some neurological disorders. Sofa potato and twitch once had mutations in genes later identified to cause human diseases [ 13 , 24 , 25 , 40 ], and physiological study of twister indicated unappreciated benefits of subunit switch in myasthenic cases [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…AChRs at NMJs comprise of five subunits (thus called pentamers): two α1 s, one β1, one δ, and one ε or γ, with the ε and γ subunits being interchangeable. The γ subunit is expressed early in development and, in mammals and fish, is replaced by the ε subunit as the animal matures [ 8 , 9 ]. A notable exception to this long-held view, which will be discussed in detail below [ 10 , 11 ] (Fig.…”
Section: Mutants Of Achr Subunitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nicotinic AChRs are pentamers composed of 21s, 1, , and  (or ) subunits, which are all specific to skeletal muscles (13). In zebrafish as well as in mammals,  subunits are expressed in larvae and change to  as the animal matures (14,15). Recent studies showed that AChRs in slow muscles of zebrafish lack / subunits and are composed of only , , and  subunits (13).…”
Section: Introductionmentioning
confidence: 99%
“…Zebrafish (Danio rerio) is a model organism that is widely used in genetics, developmental biology, medicine, pharmacology, and toxicology (reviewed in [Alestrom et al, 2006;Carvan et al, 2007;Dai et al, 2014;Kamstra et al, 2014;Lieschke and Currie, 2007;Quaife et al, 2012;Stegeman et al, 2010;Walogorsky et al, 2012]). Its widespread use is due in part to a well-studied and annotated genome, rapid development, short life cycle, and ease of genetic manipulation.…”
mentioning
confidence: 99%